Aquifer Characterization And Groundwater Potential Evaluation In The Sedimentary Rock Formation - Sazali, Mohd Asnizam (Universiti Sains Malaysia, 2017)
The study was carried out to characterize the aquifer and to evaluate ground water potential in the sedimentary rock formation. Electrical Resistivity method and drilling method was used to develop subsurface soil profile for the determination of suitable location for tube well construction. The resistivity results show hydrogeological and the distribution of inter distinctions features of the study area. The main objective of this study is to correlate the results obtain using the electrical resistivity method together with drilling method to determine the aquifer potential characteristic in the study area using the pumping test results. The electrical resistivity method was used to infer the subsurface soil layer using different types of arrays namely Pole-Dipole, Wenner and Schlumberger array. These surveys were conducted by using ABEM Terrameter LS System and the results were analysed using 2D resistivity inversion programme (RES2DINV) software. The survey alignments were conducted with maximum electrode spread of 400 m and 800 m by employing two different resistivity survey lines at the targeted zone. The images were presented in the form of two-dimensional (2D) resistivity profiles providing a clear view of the distribution of interbedded sandstone, siltstone and shale as well as potential groundwater zones. The evaluation of potential groundwater zones identified from resistivity results were confirmed by using pumping test, step drawdown test and recovery test. The combination between these three arrays and the correlation between the well log and pumping test is reliable and successful in identifying potentially favorable zones for obtaining groundwater in the study area.